Faktor Risiko Perokok dan Alkoholik terhadap Penderita Penyakit TBC - Christine J K Ekawati; Siprianus Singga; Edwin Mauguru (NHM PRESS, 2022)
Pulmonary TB is caused by the bacterium Mycobacterium tuberculosis. This disease is a contagious disease and spreads faster in men 1,4 times greater than women. The aim is to reveal the problem of risk factors that influence pulmonary TB disease, namely smokers and alcoholics. The method is that this article was written by reading a number of literature discussing pulmonary TB in relation to smoking and drinking behavior. Smokers have a 40-60 percent higher chance of developing pulmonary TB than non-smokers. An unhealthy environment can trigger a wider spread of TB, especially from TB patients who smoke. Alcohol dependence of pulmonary TB patients with smear + in the pre-alcoholic stage can climb to the next stage. At an emergency stage alcoholism can cause the body's resistance to decrease because all control is lost, even alcohol drinkers will continue until they pass out so that the social interaction of the person concerned becomes bad due to dependence on alcohol. The conclusion is that smoking and drinking alcohol are risk factors for pulmonary TB patients. There needs to be a strong motivation so that we all reduce the habit of smoking and drinking alcohol.